Comparative Analysis of Doxing Regulations and Privacy Protection in Indonesia and Global Perspectives - Rizky, Muhamad; Hamdani, Fauzie Muhammad; Anggraeni, Happy Yulia (Research Horizon, 2025)
Doxing, the unauthorized disclosure of an individual’s personal information, poses a significant threat to the right to privacy guaranteed by law in many countries. This phenomenon is increasing with the development of technology and the use of digital media. This study aims to explore the legal regulations governing doxing in Indonesia and compare them with the legal frameworks in several other countries, such as the United States, the European Union, and Australia. The method used is a normative juridical approach with a comparative analysis based on relevant legislation, legal doctrine, and case studies. The results show that in Indonesia, the Electronic Information and Transactions Law and the Draft Law on Personal Data Protection serve as the primary legal basis for personal data protection. However, these two instruments do not explicitly regulate doxing as a specific crime, creating a legal loophole that makes it difficult to prosecute perpetrators. Meanwhile, the European Union has the General Data Protection Regulation, which provides comprehensive protection and severe sanctions for privacy violations. This study recommends regulatory updates that include an explicit definition of doxing, strengthened law enforcement mechanisms, and increased public digital literacy to mitigate the risk of privacy violations.